Patients’ Satisfaction with The Quality of Health Care Services at The Mamprobi Polyclinic - Mensah, F. (University of Ghana, 2017)
Patients have become aware of the need for quality health care, and as a result, the satisfaction of patient is considered as an outcome of health care services delivered, as well as a measure of its quality. Good health in any society or community depends on the quality of health care services delivered. In addition to this, the socioeconomic status of participants, their life style/culture and their environment, play a role in ensuring good health of participants. Researchers’ observation shows that patients are dissatisfied with care being rendered to them. This study, therefore, aims at exploring patients’ satisfaction with health care services. The SERVQUAL model was used as a framework for the study. The Mamprobi Polyclinic was chosen as the site for the study. Participants for the study were selected through a purposive sampling technique from patients who attended the out -patients department (O.P.D) of the polyclinic and both genders were included. In all twelve participants, based on saturation of the study were used. Data were collected, using a semi-structured interview guide accompanied by probes to aid further exploration. Data analysis was done by thematic content analysis, and this was carried out concurrently with data collection. During the study, ethical issues were addressed by ensuring confidentiality and anonymity of all participants. In all five major the findings emerged. Three of them were related to the construct of the model. Namely; patients’ satisfaction with health care, hospital environment and facilitators/barriers to patients’ satisfaction. The remaining two were from the objectives of the study; these were the effect of patients’ satisfaction with their health seeking behaviours and needs/suggestions of patients to improve service quality. At the end of the study, it was recommended that health care providers should be trained on interpersonal skills. In conclusion, the study stressed the need for improvement in the staff strength and physical environment of the polyclinic to ensure patient satisfaction with health care services.
Keywords: Mamprobi Polyclinic; Patients’ Satisfaction; Health Care Services